Kajian Status Hara N, P, K Tanah Pada Sawah Tadah Hujan (Studi Kasus Tiga Desa di Kecamatan Beringin) - Arkhiadi Benauli (Agrosains : Jurnal Penelitian Agronomi, 2021)
Soil fertility status describes soil characteristics and soil suitability with the plants to be cultivated. This study aims to identify the variable soil fertility that becomes an obstacle in several villages in the Beringin District. This research was conducted in the villages of Aras Kabu, Kelapa, and Serdang, Beringin District, Deli Serdang Regency. This research is descriptive using the survey method. Sampling of soil in the survey area was carried out sequentially with a purposive random sampling method. The results showed that the total N status in the three villages was classified as low. Where the total N value in Aras Kabu village was 0.13%, Kelapa village 0.12% and Serdang village was 0.21%. Phosphorus in the research field is classified as high. In the village of Aras, the district was 19.57 ppm, Kelapa village 19.27 ppm and Serdang village 13.19 ppm. The K2O value in the study area was also low, where the village of Aras Kabu was only 19.96 mg K2O/100 g, Kelapa village 18.56 mg K2O/100g and Serdang village 25.47 mg K2O/100g. The use of P fertilizers can be reduced as an implication of the status of P nutrients available in high land, while to increase the low levels of N and K nutrients, it can be done by providing organic matter in the form of fertilizer (compost or cage) or returning post-harvest straw to the land.